KAJIAN TAFSIR AL-QUR’AN: Telaah atas Kitab Taisirul Lathifil Mannani fi Khulashati Tafsiril Qur`an Karya Abdurrahman bin Nashir as-Sa’di - Anshory, Muhammad Isa (Al - Tadabbur: Jurnal Ilmu Al-Qur'an dan Tafsir, 2020)
Tafsir Maudhu'i is an interpretation that seeks to explain in a more focused and clear manner because the discussion is based on themes, so that the advantages of maudhu'i interpretation are dynamic, systematic, and easy to understand as a whole. As-Sa'di is a person who concentrates his knowledge in the field of "Tafsir" (Qur'an interpretation). It proved by his work in the form of 30 juz interpretations with the title of the book "Taisir Karimir Rohman fii Kalaamil Mannan". However, as-Sa'di also wrote a commentary book that used the "Maudhu'i interpretation method, which is entitled "Taisirul Lathifil Mannani fi Khulashati Tafsiril Qur`an".As-Sa'di described it based on the theme from which the related verses were collected, making it easier for the reader to understand the contents of the al-Qur'an. The theme he chose also covered the main teachings of Islam, from the theme of aqidah, Islamic law, and the stories of the prophets contained in the al-Qur'an. The description of this commentary book is very systematic, from choosing the theme to its discussion.